Characteristics and Outcomes of Critical Illness in Children With Feeding and Respiratory Technology Dependence. Issue 5 (May 2019) - Heneghan, Julia A.; Reeder, Ron W.; Dean, J. Michael; Meert, Kathleen L.; Berg, Robert A.; Carcillo, Joseph; Newth, Christopher J. L.; Dalton, Heidi; Tamburro, Robert; Pollack, Murray M.
Abstract : Objectives: Children with dependence on respiratory or feeding technologies are frequently admitted to the PICU, but little is known about their characteristics or outcomes. We hypothesized that they are at increased risk of critical illness–related morbidity and mortality compared with children without technology dependence. Design: Secondary analysis of prospective, probability-sampled cohort study of children from birth to 18 years old. Demographic and clinical characteristics were assessed. Outcomes included death, survival with new morbidity, intact survival, and survival with functional status improvement. Setting: General and cardiovascular PICUs at seven participating children's hospitals as part of the Trichotomous Outcome Prediction in Critical Care study. Subjects: Children from birth to 18 years of age as part of the Trichotomous Outcome Prediction in Critical Care study. Interventions: None. Measurements and Main Results: Children with technology dependence composed 19.7% (1, 989/10, 078) of PICU admissions. Compared with those without these forms of technology dependence, these children were younger, received more ICU-specific therapeutics, and were more frequently readmitted to the ICU. Death occurred in 3.7% of technology-dependent patients ( n = 74), and new morbidities developed in 4.5% ( n = 89). Technology-dependent children who developed new morbidities had higher Pediatric Risk of Mortality scores and received more ICU therapies than those who did not. A total of 3.0% of technology-dependent survivors ( n = 57) showed improved functional status at hospital discharge. Conclusions: Children with feeding and respiratory technology dependence composed approximately 20% of PICU admissions. Their new morbidity rates are similar to those without technology dependence, which contradicts our hypothesis that children with technology dependence would demonstrate worse outcomes. These comparable outcomes, however, were achieved with additional resources, including the use of more ICU therapies and longer lengths of stay. Improvement in functional status was seen in some technology-dependent survivors of critical illness.